Effect of Feeding Sugarcane Bagasse-Extracted Polyphenolic Mixture on the Growth Performance, Meat Quality, and Oxidative and Inflammatory Status of Chronic Heat-Stressed Broiler Chickens - Motoi Kikusato; Fu Namai; Katsushige Yamada (Animals)
Background: This study aimed to evaluate the effects of sugarcane bagasse-extracted polyphenolic mixture (SBPM) supplementation on the harmful effects of chronic heat stress (HS) in broiler chickens. Methods: Two hundred and eighty-eight day-old male Ross 308 chicks were fed an SBPM in 0, 75, 150, or 300 ppm-supplemented diets and reared under thermoneutral (TN, 22.1–24.8 °C) or chronic HS (28.3–36.2 °C) conditions from 11 d to 42 d. Results: The chronic HS treatment negatively affected body weight, feed intake, and feed conversion ratio (p < 0.05), and these changes were partially attenuated by the SBPM supplementation (p < 0.05). Plasma lipid peroxidation content, inflammatory cytokines [interleukin (IL)-6, IL-β], corticosterone, and uric acid concentrations were significantly increased by HS, and these increases were attenuated by the SBPM supplementation (p < 0.05). Intestinal permeability indicator and serum fluorescein isothiocyanate-dextran levels after oral gavage were increased by HS and were also suppressed by the supplementation (p < 0.05). The HS-decreased muscle drip loss, lipid peroxidation, and glutathione content were also suppressed by the SBPM supplementation. The abovementioned alleviating effects of the SBPM were of a dose-dependent manner in most cases. Conclusion: This study demonstrated that SBPM supplementation can improve the growth performance, meat quality, inflammation, and intestinal permeability of chronic HS-treated broiler chickens.